Improving the quality of guidance and counseling services through android-based data collection information technology - Idris, Idriani; Sari, Permata; Idris, Nur Idil Fitri; Utami, Ferisa Prasetyaning (Universitas Islam Negeri Raden Intan Lampung, 2024)
Services have a vital role in helping students face various challenges. However, conventional services often encounter obstacles, especially with the increasing number of students requiring guidance. This research aims to enhance the quality of guidance and counseling services through the implementation of Android-based information technology for student data collection. This study employs the ADDIE development model. The analysis phase is carried out through expert testing. The developed application is designed with consideration for data security, user privacy, as well as ease of access and service flexibility. Evaluation is conducted through feasibility tests by experts in guidance and counseling, media, and information technology, along with trials involving end-users. The research results indicate that the Android-based data collection system received high ratings in feasibility, accuracy, ease of use, and usability. The implementation of this system enables administrative efficiency, more measurable student progress monitoring, and the provision of more personalized and responsive services.